Identification of Novel Prognostic Biomarkers Relevant to Immune Infiltration in Lung Adenocarcinoma - Xia, Zhi; Rong, Xueyao; Dai, Ziyu; Zhou, Dongbo (Frontiers in Genetics, 2022)
Abstract Background: Programmed death ligand-1 (PD-L1) is a biomarker for assessing the immune microenvironment, prognosis and response to immune checkpoint inhibitors in the clinical treatment of lung adenocarcinoma (LUAD), but it does not work for all patients. This study aimed to discover alternative biomarkers. Methods: Public data were obtained from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). Weighted coexpression network analysis (WGCNA) and gene ontology (GO) were used to determine the gene modules relevant to tumor immunity. Protein–protein interaction (PPI) network and GO semantic similarity analyses were applied to identify module hub genes with functional similarities to PD-L1, and we assessed their correlations with immune infiltration, patient prognosis and immunotherapy response. Immunohistochemistry (IHC) and hematoxylin and eosin (H&E) staining were used to validate the outcome at the protein level. Results: We identified an immune-response-related module, and two hub genes (PSTPIP1 and PILRA) were selected as potential biomarkers with functional similarities to PD-L1. High expression levels of PSTPIP1 and PILRA were associated with longer overall survival and rich immune infiltration in LUAD patients, and both were significantly high in patients who responded to anti-PD-L1 treatment. Compared to PD-L1 negative LUAD tissues, the protein levels of PSTPIP1 and PILRA were relatively increased in PD-L1 positive tissues, and the expression of PSTPIP1 and PILRA positively correlated with tumor-infiltrating lymphocytes. Conclusion: We identified PSTPIP1 and PILRA as prognostic biomarkers relevant to immune infiltration in LUAD, and both are associated with the response to anti-PD-L1 treatment.